Correlation between labour standards and international trade : which way forward? - Addo, Kofi (2002)
Provides a brief history of the linkage between trade and labour standards, and defines core labour standards. Examines the views of the proponents of a linkage between trade and labour standards. Focuses on arguments against the imposition of trade sanctions on countries that do not respect the core labour standards. Analyzes the views of the critics of sanctions imposition.